Digging deeper: Insights into metallurgical transitions in European prehistory through copper isotopes. (December 2017) - Powell, Wayne; Mathur, Ryan; Bankoff, H. Arthur; Mason, Andrea; Bulatović, Aleksandar; Filipović, Vojislav; Godfrey, Linda
Abstract: Southeastern Europe is the birthplace of metallurgy, with evidence of copper smelting at ca. 5000 BCE. There the later Eneolithic (Copper Age) was associated with the casting of massive copper tools. However, copper metallurgy in this region ceased, or significantly decreased, centuries before the dawn of the Bronze Age. Archaeologists continue to be debate whether this hiatus was imposed on early metalworking communities as a result of exhaustion of workable mineral resources, or instead a cultural transition that was associated with changes in depositional practices and material culture. Copper isotopes provide a broadly applicable means of addressing this question. Copper isotopes fractionate in the near-surface environment such that surficial oxide ores can be differentiated from non-weathered sulphide ores that occur at greater depth. This compositional variation is transferred to associated copper artifacts, the final product of the metallurgical process. In the central Balkans, a shift from 65Cu-enriched to 65Cu-depleted copper artifacts occurs across the metallurgical hiatus at the Eneolithic-Bronze Age boundary, ca. 2500 BCE. This indicates that the reemergence of metal production at the beginning of the Bronze Age is associated with pyrotechnical advancements that allowed for the extraction of copper from sulphide ore. Thus copper isotopes provide direct evidence that the copper hiatus was the result of exhaustion of near-surface oxide ores after one-and-a-half millennia of mining, and that the beginning of the Bronze Age in the Balkans is associated with the introduction of more complex smelting techniques for metal extraction from regionally abundant sulphidic deposits. Highlights: Copper isotopic analysis of copper and bronze artifacts can determine whether the metal was smelted from oxide or sulphidic ores. Serbian Eneolithic and Bronze Age artifacts were manufactured from malachite-bearing ore and sulphide ore, respectively. The Late Eneolithic copper hiatus in the central Balkans was due to exhaustion of malachite ore reserves. The onset of the Bronze Age in Serbia corresponds to the introduction of sulphide smelting technology.